Grievance Politics: An Empirical Analysis of Anger Through the Emotional Mechanism of Ressentiment - Capelos, Tereza (2022)
In this article, we undertake an empirical examination of the psychology of what is often called “the angry citizen,” highlighting ressentiment as an important emotional mechanism of grievance politics. Contrary to the short‐lived, action‐prone emotion of anger proper, ressentiment transmutes the inputs of grievance politics like deprivation of opportunity, injustice, shame, humiliation, envy, and inefficacious anger, into the anti‐social outputs of morally righteous indignation, destructive anger, hatred, and rage. Our empirical probe uses qualitative and quantitative analysis of 164 excerpts from interviews with US “angry citizens” from the following works: Strangers in Their Own Land: Anger and Mourning on the American Right (2016) by Arlie Russell Hochschild, Angry White Men: American Masculinity at the End of an Era (2017) by Michael Kimmel, and Stiffed: The Roots of Modern Male Rage (2019) by Susan Faludi. In these seemingly “angry” excerpts, we find markers matching the psychological footprint of ressentiment instead of anger proper: victimhood, envy, powerlessness; the defenses of splitting, projection, and denial; and preference for inaction, anti‐preferences, and low efficacy. We conclude on the significance of the distinction between anger proper and ressentiment for understanding the psychology of grievance politics.